Innovative Progress in Bacterial Cellulose for Biomedical Applications - Berton, Sharise; Rafael, Lívia Mainardes; Ferreira, Vinícius Campos; Berton Junior, Jomar (Orbital: The Electronic Journal of Chemistry, 2025)
Advances in science materials and the development of biopolymers have gained attention mainly as a substitute for traditional plastic. Bacterial cellulose (BC) is a great candidate as it is a very important biopolymer with possible biocompatibility, non-toxic and sterilizable, and can be used in several biomedical applications. This article presents a bibliometric search of scientific documents showing the growth of research related to the use of this material in biomedicine emphasizing BC as a substitute for plastic. Original research articles and review articles published up to 2023 were considered, resulting in 330 documents. The work focused on titles and abstracts that contained the chosen keywords related to the topic in question. The results of the investigation emphasize the necessity of more research in the area and a greater need of collaboration. Studies have shown the potential for the use of bacterial cellulose in wound healing, tissue repair, and other healthcare applications. Therefore, the results of the investigation emphasize the need for more research in the area and also highlight the need for greater collaboration.